An up-to-date overview of the most recent transcatheter implantable aortic valve prostheses. (2nd January 2016) - Wiegerinck, Esther M.A.; Van Kesteren, Floortje; Van Mourik, Martijn S.; Vis, Marije M.; Baan Jr, Jan
Abstract : Over the past decade transcatheter aortic valve implantation (TAVI) has evolved towards the routine therapy for high-risk patients with severe aortic valve stenosis. Technical refinements in TAVI are rapidly evolving with a simultaneous expansion of the number of available devices. This review will present an overview of the current status of development of TAVI-prostheses; describes the technical features and applicability of each device and the clinical data available.